The role of worm infestation in allergic rhinitis - Manuel, A.M.; Kuljit, S.; Gopalakrishnan, G.; Suresh, K.G.; Balraj, P. (2012)
The purpose of this study is to determine the relevance of the hygiene hypothesis; that is to determine if worm infestation has a protective role against the development of allergic rhinitis. A prospective case controlled study was conducted. Specific IgG levels to Toxocara were studied in 85 patients confirmed to have allergic rhinitis and were compared to levels in another 85 controls, with no form of allergy. The IgG assay was done using ELISA technique. There was a higher incidence of positive specific IgG to Toxocara in the controls as compared to allergic patients. The values were statistically significant Chi square test (p=0.002). This negative association between worm infestation and allergic rhinitis suggests that a previous worm infestation could protect against the development of allergic rhinitis.